2021
DOI: 10.1101/2021.08.20.21262082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Natural Language Processing to Classify Serious Illness Communication with Oncology Patients

Abstract: One core measure of healthcare quality set forth by the Institute of Medicine is whether care decisions match patient goals. High-quality “serious illness communication” about patient goals and prognosis is required to support patient-centered decision-making, however current methods are not sensitive enough to measure the quality of this communication or determine whether care delivered matches patient priorities. Natural language processing (NLP) offers an efficient method for identification and evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Clinical notes and electronic medical records were the most common primary data sources, used in 57 studies (69.5%). 21,2327,29,30,3336,40,42–46,4852,54,55,5764,6668,70–73,75,7993,95 Other primary sources included audio recordings ( n = 6, 7.3%), 6,28,32,38,39,65 administrative data ( n = 5, 6.1%), 37,47,53,77,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical notes and electronic medical records were the most common primary data sources, used in 57 studies (69.5%). 21,2327,29,30,3336,40,42–46,4852,54,55,5764,6668,70–73,75,7993,95 Other primary sources included audio recordings ( n = 6, 7.3%), 6,28,32,38,39,65 administrative data ( n = 5, 6.1%), 37,47,53,77,...…”
Section: Resultsmentioning
confidence: 99%
“…These applications offer the possibility of several toolkits for natural language processing and also the possibility to develop codes based on the researchers' needs. Another interesting finding was that many of the studies used a combination of more than one 27 Elhazmi et al, 33 Ganguli et al, 36 George et al, 37 Hu et al, 44 Kehl et al, 48 Laios et al, 50 Lin et al, 57 Manz et al, 66 Agarwal et al, 74 Santos et al, 77 Sung et al, 82 Ye et al 93 Assessment of the impact of interventions 9 (10.9) Ando et al, 22 Greer et al, 42 Lakin et al, 51 Lefèvre et al, 56 Macieira et al, 64 Santarpia et al, 76 Steiner et al, 80 Udelsman et al, 87 Uyeda et al 89 Social and spiritual health 8 (9.7) Gray et al, 40 Johnson et al, 46,47 Masukawa et al, 67 Yoon et al, 94 Ando et al, 96 Ando et al 99 Topic identification 8 (9.7) Sarmet et al, 5 Ando et al, 21 Chan et al, 26 Davoudi et al, 29 Agaronnik et al, 52 Lucini et al, 61 Seale et al, 78 Wang et al 90 Advance care planning/EOL process measures/Code-status clarification/Goals of care documentation 8 (9.7)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, relying on Natural Language Processing (NLP) methods, we present an automatic classifier to retrieve GOC discussions in the EHR that may facilitate both clinicians’ point-of-care access to their patients’ documented goals (or lack thereof) and arduous data extraction processes for research. Recent studies have employed various NLP methods to identify GOC discussions in the EHR Chan et al (2019); Lee et al (2021); Davoudi et al (2022) in different care settings and seriously ill populations. All of the studies reported good overall model performance in internal validation cohorts and a substantial reduction in human annotation time for EHR review.…”
Section: Significance and Backgroundmentioning
confidence: 99%
“…NLP is ubiquitous in consumer life, with uses ranging from predictive text on our smartphones and emails to automated voice assistants such as Siri and Alexa. We have only begun exploring uses of NLP in healthcare; so far, its applications include predicting admissions of patients in the emergency department, identifying patients suitable for clinical trials, mining medical records to predict treatment efficacy and adverse events, and analyzing the quality and comprehensiveness of clinical documentation, to name a few ( 8 11 ).…”
mentioning
confidence: 99%